2015
DOI: 10.1371/journal.pone.0143018
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic Survey of Potential Pathogens in Obligate and Facultative Scavenging Avian Species in California

Abstract: Throughout the world, populations of scavenger birds are declining rapidly with some populations already on the brink of extinction. Much of the current research into the factors contributing to these declines has focused on exposure to drug residues, lead, and other toxins. Despite increased monitoring of these declining populations, little is known about infectious diseases affecting scavenger bird species. To assess potential infectious disease risks to both obligate and facultative scavenger bird species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…However, this lack of difference could also be associated with the fact that black vultures can acquire this pathogen from different bird species in multiple sites, including anthropogenic and wild areas. For instance, black vultures can acquire Chlamydia psittaci when interacting with other bird species that could be infected by this pathogen and may act as carriers such as gulls (Franson & Pearson, ; Harkinezhad, Geens, & Vanrompay, ), Turkey vultures (Cathartes aura) (Straub et al., ), birds of prey or different water birds (Harkinezhad et al., ; Kaleta & Taday, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this lack of difference could also be associated with the fact that black vultures can acquire this pathogen from different bird species in multiple sites, including anthropogenic and wild areas. For instance, black vultures can acquire Chlamydia psittaci when interacting with other bird species that could be infected by this pathogen and may act as carriers such as gulls (Franson & Pearson, ; Harkinezhad, Geens, & Vanrompay, ), Turkey vultures (Cathartes aura) (Straub et al., ), birds of prey or different water birds (Harkinezhad et al., ; Kaleta & Taday, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hagen et al (2002) found a low seroprevalence against M. gallisepticum in lesser prairie-chickens in Kansas but could not rule out the hypothesis of a non-specific reaction. Straub et al (2015) reported a 1% seroprevalence for M. gallisepticum in free-flying Californian condors and a 57% seroprevalence for captive birds. However, these authors did not report observation of clinical signs on these birds.…”
Section: Gallisepticummentioning
confidence: 99%
“…Straub et al. () reported a 1% seroprevalence for M. gallisepticum in free‐flying Californian condors and a 57% seroprevalence for captive birds. However, these authors did not report observation of clinical signs on these birds.…”
Section: Assessmentmentioning
confidence: 99%
“…The parasite can cause mortality and subclinical infection among many animal species, including birds (DUBEY, 2010). Although there have been reports of T. gondii infection in scavenging birds (ARENE, 1999;SALANT et al, 2013;STRAUB et al, 2015), we are unaware of any reports on T. gondii infection in black vultures. The present study aimed at determining the presence of T. gondii antibodies in wild black vultures (Coragyps atratus) in Brazil.…”
mentioning
confidence: 92%
“…Regarding another vulture species, the turkey vulture (Cathartes aura) in the USA, one of the two birds examined presented T. gondii antibodies when tested using the indirect hemagglutination test (FRANTI et al, 1975). Also studying the same species of vultures, in California Straub et al (2015) found 11% positivity (7/66 using a commercial agglutination test (cutoff ≥ 32).…”
mentioning
confidence: 99%